First Three Cal Poly Buildings with Household Arts Building Under Construction (1906)
The first three buildings at the California Polytechnic School, designed by architect William Weeks. Administration Building, Center, Dormitory No. 1 on the right and the Household Arts Building on the left, under construction. The household arts building was built in 1906. Photo can also be found here: http://digital.lib.calpoly.edu/rekl-4161